2022
DOI: 10.1002/met.2102
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution climate characteristics of the Arabian Gulf based on a validated regional reanalysis

Abstract: The regional climate of the Arabian Gulf (AG) and its variability are examined based on a 40-year (1980-2019), 5-km regional reanalysis of the Arabian Peninsula (AP reanalysis). The AP reanalysis fields were first validated against the available observations over the AG, suggesting that this high-resolution reanalysis well reproduces the spatio-temporal features of the AG atmospheric circulations. The validated AP reanalysis fields were then analysed to examine the climatic characteristics over the AG includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 82 publications
0
0
0
Order By: Relevance
“…After 22 LT, the CO 2 values decrease as the land-breeze advects cleaner (i.e., less CO 2 -rich) desert air into the site. As the local-scale circulations (e.g., Dasari et al, 2022) and the spatial distribution of CO 2 emissions (e.g., Farahat, 2016) in the Arabian Peninsula are highly heterogeneous, the variability of the CO 2 concentration on different timescales throughout the region is likely to differ from that of the station near Kuwait City mentioned above. A network of surface CO 2 observations is therefore needed to evaluate the estimates from remote sensing assets, which can exhibit considerable biases (e.g., Kulawik et al, 2016), and to further our understanding on the processes behind the observed variability.…”
Section: Introductionmentioning
confidence: 99%
“…After 22 LT, the CO 2 values decrease as the land-breeze advects cleaner (i.e., less CO 2 -rich) desert air into the site. As the local-scale circulations (e.g., Dasari et al, 2022) and the spatial distribution of CO 2 emissions (e.g., Farahat, 2016) in the Arabian Peninsula are highly heterogeneous, the variability of the CO 2 concentration on different timescales throughout the region is likely to differ from that of the station near Kuwait City mentioned above. A network of surface CO 2 observations is therefore needed to evaluate the estimates from remote sensing assets, which can exhibit considerable biases (e.g., Kulawik et al, 2016), and to further our understanding on the processes behind the observed variability.…”
Section: Introductionmentioning
confidence: 99%
“…The model was forced with atmospheric fields of 5-km horizontal resolution generated by downscaling the ERA-Interim reanalysis (Dee et al, 2011) using the advanced research version of the weather research and forecasting (WRF) model, assimilating all available satellite and conventional observations in the region (Hoteit et al, 2021). It is important to note that the generation of these atmospheric fields was conducted independently of our study and is extensively described in Viswanadhapalli et al (2017) and Dasari et al (2022). Furthermore, comprehensive validations of these fields against available observations have been conducted and presented in Langodan et al (2017) and Viswanadhapalli et al (2017).…”
mentioning
confidence: 99%